Re-pressed: How Serigraphy Re-envisions Northwest Coast Iconography - Young, India (ARTiculate, 2012)
In 1986 Andy Warhol silkscreened a series of cowboys and Indians.  In 1978 Roy Henry Vickers, a Tsimshian artist, silkscreened Jesus as well as a lacrosse player.  Since the time of the Campbell’s Soup Can (1962), Northwest Coast Indigenous artists have been silkscreening fine art in their own vernacular.  They have used the medium to reclaim heritage, to share histories, to educate, and to demand Western recognition through visuality.  Today, as Western serigraphy has receded back to the commercial medium it was before Pop art, Indigenous artists continue to envision the possibilities serigraphy provides to challenge the art world and popular perceptions of Indigenous cultures.  In this paper I reveal the modes of discourse opened through Indigenous people’s use of serigraphy.  Since its inception into Northwest Coast culture, the serigraph has been used to tell the story of Northwest Coast tradition and progress: politically, economically, artistically and culturally.